1978
DOI: 10.1007/bf01476669
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial cells in acute myocardial infarction and angina pectoris

Abstract: The authors have counted circulating anuclear carcasses of endothelial cells by a new method in 105 patients with acute myocardial infarction and angina pectoris. In infarction cases as well as in severe angina a significant increase of endothelaemia was observed in duration of several days. No increase was observed in milder angina cases (type I--II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 1 publication
0
38
0
2
Order By: Relevance
“…Одним из таких быстрых и достоверных методов является определение десквамированных эндо-телиоцитов в плазме. Данный метод зарекомендовал себя при большинстве сердечно-сосудистых заболеваний: ги-пертонической болезни [48], острой и тяжелой ХСН [48,39], ИМ и нестабильной стенокардии [49,50], стабильной сте-нокардии [33], легочной гипертензии [45], причем тя-жесть заболевания напрямую связана с количеством эндо-телиоцитов.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Одним из таких быстрых и достоверных методов является определение десквамированных эндо-телиоцитов в плазме. Данный метод зарекомендовал себя при большинстве сердечно-сосудистых заболеваний: ги-пертонической болезни [48], острой и тяжелой ХСН [48,39], ИМ и нестабильной стенокардии [49,50], стабильной сте-нокардии [33], легочной гипертензии [45], причем тя-жесть заболевания напрямую связана с количеством эндо-телиоцитов.…”
Section: Resultsunclassified
“…The count of desquamated endotheliocytes is one of such quick and reliable methods. The procedure is successfully used in majority of cardiovascular diseases: HT [48], acute and severe CHF [48,39], myocardial infarction and unstable [49,50] and stable angina [33], pulmonary hypertension [45]. At that the disease severity directly correlates with the number of endotheliocytes.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study has demonstrated the elevated microparticles derived from apoptotic endothelial cells (ECs) in the circulating blood of the patients with ACS . Additionally, high levels of circulating apoptotic ECs were present in patients with myocardial infarction and angina (Hladovec et al 1978;Mutin et al 1999). It has been also reported that endothelial apoptosis may directly affect blood thrombogenicity through the release of apoptotic microparticles into the bloodstream (Mallat and Tedgui 2001).…”
mentioning
confidence: 99%
“…All these studies mentioned above suggest a relationship between endothelial apoptosis and endothelial denudation and thrombosis (Hladovec et al 1978;Bombeli et al 1997;Bombeli et al 1999;Mutin et al 1999;Mallat and Tedgui 2001); however, direct evidence to link these events is still lacking. Thus, the aim of the present research is to provide this evidence using a rabbit model of atherosclerosis.…”
mentioning
confidence: 99%
“…ECs have since been shown to line a ventricular assist device [11]. In this context it is interesting that circulating ECs are detectable in diseases marked by vascular injury, namely sickle cell anemia, acute myocardial infarction, thrombotic thrombocytopenic purpura, and active cytomegalovirus infection [12][13][14][15]. Normal adults have 2.6±1.6 circulating ECs per mm of peripheral blood [15].…”
Section: Differences Between Epcs and Circulating Ecsmentioning
confidence: 99%